FIQIH MUAMALAH PERSPECTIVE ON THE DETERMINANT FACTORS OF THE DECISION TO USE SHOPEEPAY LATER THROUGH SHOPPING CONVENIENCE - Rabiatul Adawiyah; Andi Martina Kamaruddin; Mukhtar Muhammad Salam (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Raden Fatah Palembang, Indonesia, 2024)
This study aims to determine the role of ease of shopping in mediating the influence of understanding usury, and product knowledge on the decision to use shopeepay later reviewed from the perspective of muamalah fiqh. The population in this study were students of Mulawarman University, Sharia Economics Study Program, totaling 330 people. The sample was taken using the Arikunto formula, which ranged from 10% - 15% or 20% - 25% so that a sample of 36 students was obtained. The analysis technique used SEM PLS with outer model testing including validity tests, reliability tests and inner models including F square, R Square and Estimate For Path Coefficients. The results showed that the ease of shopping variable had a direct effect on decisions while understanding usury did not have a direct effect on decisions, and the product knowledge variable did not have a direct effect on decisions. The understanding of usury variable had a direct effect on ease of shopping while product knowledge did not have a direct effect on ease of shopping. The ease of shopping variable was unable to mediate the influence between understanding usury on decisions, as well as ease of shopping was unable to mediate the influence between product knowledge on decisions. The conclusion shows that only the ease of shopping variable directly influences the decision and only the understanding of usury variable directly influences the ease of shopping. Then the ease of shopping variable is unable to mediate the influence of understanding usury and product knowledge on the decision.